The Improvement of Luminous Uniformity of Large-Area Organic Light-Emitting Diodes by Using Auxiliary Electrodes - Fuh-Shyang Juang; Jia-You Chen; Wen-Kai Kuo; Krishn Das Patel (Photonics, 2024)
The study developed a large emission area of flexible blue organic light-emitting diodes (BOLED) on a polyethylene terephthalate/ Indium tin oxide (PET/ITO) substrate using a polycyclic skeleton ν-DABNA Thermally Activated Delayed Fluorescence (TADF) material. Initially, a 1 × 1 cm2 blue OLED was fabricated to optimize the layer thickness. The blue OLED structure consisted of PET/ITO/HATCN/TAPC/UBH-21:ν-DABNA/TPBi/LiF/Al. However, as the emission area increased to 3.5 × 3.5 cm2, the current density decreased due to the resistance of PET/ITO, leading to luminance non-uniformity. To address this issue, auxiliary Au lines were added to the ITO anode to enhance current injection. Despite this, when the Au lines reached a thickness of 30 nm, average light emission was disrupted. To improve the luminescence characteristics of large-area PET/ITO OLEDs, a capping and planarization layer of PEDOT:PSS was applied. Grid uniformity revealed a significant increase in overall luminance uniformity from 74.1% to 87.4% with the addition of auxiliary Au lines. Further increases in grid line density slightly reduced uniformity but enhanced brightness, resulting in brighter, flexible, large-area blue OLED lighting panels.